2007
DOI: 10.1021/es070152v
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Beta Blockers to Environmental Surfaces

Abstract: Beta-adrenergic blocking agents (beta blockers) are widely used pharmaceuticals which have been detected in the environment. Predicting the transport and ultimate fate of beta blockers in the environment requires understanding their adsorption to soils and sediments, something for which little information is currently available. The objective of this work was to examine the adsorption of three beta blockers, propranolol, metoprolol and nadolol, to a natural alluvial material, as well as to six minerals present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 22 publications
3
38
1
Order By: Relevance
“…Experimental studies of 11 β-blockers indicated very low gastric absorption rate for these drugs; however, their intestinal and colonic absorption rates were of the same magnitude between 0.12 and 4.28 hour -1 (Vilà et al 1992). Hydrophobicity is an important predictor of β-blocker adsorption; propranolol is the most hydrophobic β-blocker studied, which was adsorbed to the greatest extent (Kibbey et al 2007). Atenolol (AT) is one of the most commonly prescribed β-blockers with a low hydrophobicity or lipophilicity with a log K OW of only 0.1, suggesting a low affinity for solid substrates (Küster et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies of 11 β-blockers indicated very low gastric absorption rate for these drugs; however, their intestinal and colonic absorption rates were of the same magnitude between 0.12 and 4.28 hour -1 (Vilà et al 1992). Hydrophobicity is an important predictor of β-blocker adsorption; propranolol is the most hydrophobic β-blocker studied, which was adsorbed to the greatest extent (Kibbey et al 2007). Atenolol (AT) is one of the most commonly prescribed β-blockers with a low hydrophobicity or lipophilicity with a log K OW of only 0.1, suggesting a low affinity for solid substrates (Küster et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the reported sieve size fractions of the Ottawa sand used in the test(s) and assuming the sand grains were spherical, a geometric specific surface area of ~100 cm 2 /g is calculated for the sand. Alternatively, gas adsorption surface areas (Brunauer-Emmet-Teller method) for Ottawa sand have been reported to be in the 900 to 1000 cm 2 /g range (Kibbey et al 2007;Reimus et al 2010). Using a range of specific surface areas from 100 to 1000 cm 2 /g along with the sand masses, pore volumes, and observed Saf-T retardation factor of ~1.1 at 160 ο C (the highest temperature tested) in the experiments of Leecaster et al (2012), Sa-T K a values ranging from 2.3e-5 cm 3 /cm 2 to 2.3e-4 cm 3 /cm 2 are estimated from Equation (6.1).…”
Section: Semi-analytical Model Analysismentioning
confidence: 99%
“…We intuitively expect that it is more likely that the effective specific surface area will be larger than 35,000 cm 2 /g rather than smaller because the tuffs are likely to contain minerals that are more sorptive per unit surface area than the quartz sand, which would result in a larger effective specific surface area. We also assume a specific surface area of 950 cm 2 /g for the Ottawa sand used by Leecaster et al (2012), which is the average of gas adsorption measurements on Ottawa sand reported by others (Kibbey et al 2007;Reimus et al 2010). Assuming this specific surface area for the Ottawa sand, we calculate a K a value of 2.4e-4 cm 3 /cm 2 for Saf-T using Equation (6.1) and the experimental results of Leecaster et al (2012).…”
Section: Sorption Surface Areamentioning
confidence: 99%
“…Like many other pharmaceutical compounds, these beta-blockers too are partially metabolized in the human body and are released into the environment as a mixture of unaltered molecules with its metabolites along with human waste [80]. Beta blockers are important pharmaceutical compounds for which little environmental adsorption data exists [81]. Like many pharmaceuticals, beta-blocker compounds have the potential to be highly persistent [82,83] and toxic in the environment.…”
Section: Pharmaceuticals As Pollutantsmentioning
confidence: 99%
“…This could affect their transport, degradation time and even reduce chances of exposure to these compounds. Hydrophobicity was found to be a good measure of adsorption and propranolol (PROP) was the one of the most hydrophobic beta blockers studied (compared with metoprolol and nadolol) [81]. PROP is a commonly used β-blocker that inhibits β1 and β2 adrenergic receptors in the heart, aimed at decreasing heartbeat and contractility.…”
Section: Pharmaceuticals As Pollutantsmentioning
confidence: 99%